2020
DOI: 10.1155/2020/8834507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Shape and Content of Steel Fiber on Mechanical Properties of Concrete

Abstract: Steel fiber reinforced concrete (SFRC) has gained popularity in the last decades attributed to the improvement of brittleness and low tensile strength of concrete. This study investigates the effect of three shapes of steel fibers (straight, hooked end, and corrugated) with four contents (0.5%, 1%, 1.5%, and 2%) on the mechanical properties (compression, splitting tension, shear, and flexure) of concrete. Thirteen groups of concrete were prepared and investigated experimentally. Test results indicated that ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…The results showed that the steel-fiber-reinforced UHPC presented the best performance with the hooked shape at a volume fraction of 2%. However, Zhang et al [26] found a different result. In the work of Zhang et al, the corrugated steel fiber had the best reinforced effect on the strength of concrete.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results showed that the steel-fiber-reinforced UHPC presented the best performance with the hooked shape at a volume fraction of 2%. However, Zhang et al [26] found a different result. In the work of Zhang et al, the corrugated steel fiber had the best reinforced effect on the strength of concrete.…”
Section: Introductionmentioning
confidence: 94%
“…It was reported that the properties were greatly influenced by the aspect ratio [22,23], tensile strength [23], shape [24][25][26][27], and volume content [28][29][30] of steel fibers, and the shape and volume content are the two most frequently studied factors. Generally, the strength of RPC or UHPC improves gradually with the increase of steel fiber content [31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete is one of the most widely used material in the construction industry because it offers good strength and durability properties, and its primary constituents are readily available and cheap [1][2][3]. Despite its numerous advantages, concrete is also well known to have several weaknesses, such as a low tensile strength capacity that is significantly lower than its higher capacity to resist compressive loading, brittleness, low postcracking capability, and low fracture resistance [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many types of fibre reinforced concrete (FRC), including steel and synthetic materials, have been investigated to serve as a material that can partially or fully substitute for RC in structures [17][18][19][20][21][22]. In particular, steel fibre reinforced concrete (SFRC) is becoming increasingly used in structures because it has advantages over RC in terms of increasing cracking resistance and residual strength of cracked concrete due to the fibres bridging effect [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%